Sextortion, Gender, and Digital Crime: A Socio-Legal Comparison between Positive and Islamic Law - JM. Muslimin; Shubhan Shodiq; Kamarusdiana; Thamer Hamdi M. Almutairi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
Digital sexual violence with the motive of extortion, known as sextortion, is one of the gender-based violence online types that is rampant in nowadays era of technology. The purpose of this study is to analyze (theoretically and empirically) the sextortion while offering progressive socio-legal interpretation solutions. This study is a normative and empirical legal research, employing statutory, case study, interviews, Focus Group Discussion (FGD), and fiqh approach. The data sources both primary and secondary, consist of legal materials, cases, real experiences, and sociological overviews on some relevant points. The data analysis technique used is content analysis, socio-legal explorations, and surveys, namely by examining documents in the form of legislation and related court decisions, expert judgments and empirical views of the purposive expert community. The results of the study show that positive law still has a dual attitude in which digital sexual violence with extortion motives is considered a crime on one hand but resulting in weak sanctions on another. Women are potentially oppressed and extorted, while their cultural defense mechanism is structurally weak. Meanwhile, in Islamic law, sextortion can be categorized as a part of jarīmah (criminal act) with a punishment named ta’zīr, in which the government becomes the one who determines the type of punishment. A progressive socio-legal interpretation is therefore necessary for that specific type of crime.